Oaths and Vows: Words as Genesis - Seligman, Adam B. (Walter De Gruyter GmbH, 2024)
Intro -- Contents -- List of Illustrations -- Acknowledgments -- Note on Texts and Translations -- Personal Prologues -- Introduction -- Part One: The Power of the Word -- Chapter One Prolegomena: On Oaths and Vows -- Chapter Two Obligating God -- Chapter Three The Problem of Intentionality: Short Studies -- Part Two: Desire and the Word -- Chapter Four Eros, Ananke and the Gendered Oath -- Chapter Five Eros and Oath -- Chapter Six Oath and Eros -- Chapter Seven Apophatic Love and the Paucity of Oaths in the Eastern Church -- Conclusion -- Sources -- Bibliography -- Index.